Pengaruh Informasi Arus Kas, Laba Kotor, Ukuran Perusahaan, Return On Asset (Roa) Dan Debt Equty Ratio (Der) Terhadap Return Saham (Studi Empiris pada Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Anjani, Juwita Rini Dwi, Dra. Mujiyati, M.Si (2016)
This research aims to analyze the effect of cash flow information, company size, gross profit, Return On Assets (ROA), and the Debt Equity Ratio (DER) against the return of shares on the company's wide range of industry sectors listed on the Indonesia Stock Exchange period 2012-2014. This research using a sample company 39 sectors a wide range of industries from 2012-2014 registered in Indonesia Stock Exchange (IDX). The sample was selected using the method of purposive sampling. Types of data used are secondary data. Data analysis using descriptive statistics, classic assumption test and multiple regression analysis. The variables used in this study is the operating cash flow, cash flow investment, cash flow funding, gross profit, the size of the company, Return On Assets (ROA), and the Debt Equity Ratio (DER) as the independent variable, the dependent variable as a stock return. The results of this study indicate that the operating cash flows, the cash flows of investment, Return On Assets (ROA), and the Debt Equity Ratio (DER) effect significantly to return the shares. Meanwhile variable cash flow funding, gross profit, and the size of the company do not affect significantly to return the shares. Keywords: Stock return, operating cash flow, cash flow, cash flow investment funding, gross profit, the size of the company, Return On Assets and Debt Equity Ratio.